The Bibliometric Analysis of Life Science and Social Studies Teaching with Art Studies - Atasoy, Meltem; Güllühan, Nur Ütkür; Bekiroğlu, Derya (Mimbar Sekolah Dasar, 2025)
This study investigates the limited integration of art into life sciences and social studies education in Turkey, despite these subjects being designed to reflect real-life experiences and social contexts. The primary aim is to identify research trends on this topic through descriptive, content-based bibliometric analysis. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a total of 318 academic studies, including theses and peer-reviewed articles, were systematically reviewed. Data was analyzed according to publication year, research type, method and design, study group, grade level, sample size, and art branch. Results show that publication activity peaked in 2019, with the majority of studies being master’s theses. Most research focused on 7th-grade students, involved small samples (0–30 or 31–60 participants), and employed qualitative or experimental designs. Drama emerged as the most integrated art form. These findings reveal a growing academic interest in interdisciplinary approaches, while also underscoring the need for broader exploration of underrepresented art branches in life sciences and social studies education. The results highlight a growing scholarly interest in interdisciplinary approaches, while simultaneously revealing significant gaps in the representation of diverse art forms. These findings underscore the need for future research to adopt broader methodological diversity, include larger and more varied participant groups, and expand the scope of artistic integration to enrich both cognitive and socio-emotional dimensions of learning in life sciences and social studies education.